(3bVGA GdZdh Hjf GdEHbGA hGdEdZGA aj GdbGfhf GddjHj (B: s (3OQGSI ebGQfI HGdbGfhf GdeUQj (B/ s - (3LeGd GdgGOj YeQ GdbehOjs; (3jMji YHOGdYRjR GdLed (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI ,s, 2014)
(3JfGhd ehVhY GdOQGSI (B: (3bVGA GdZdh Hjf GdEHbGA hGdEdZGA aj GdbGfhf GddjHj (B((3OQGSI ebGQfI HGdbGfhf GdeUQj(B). (3gPG hbO HOCJ GdOQGSI HebOeI hJdGgG HGHjf eSJbdjf SHbgeG HGH JegjOj (B: (3LGA GdHGH GdJegjOj HYfhGf JCUjd CMcGe bVGA GdZdh (B: (3HMKfG aj GdaUd GdChd GdeaGgje hGdCMcGe GdYGeI dbVGA GdZdh (B: (3hGSJYQVfG aj aUdg GdKGfj GdJCUjd GdbGfhfj ddQbGHI GdbVGFjI Ydi GdZdh(B: (3ef LGfH BNQ JfGhdJ GdOQGSI aj GdHGH GdChd(B: (3bVGA GdZdh Hjf GdSdWI GdJbOjQjI ddEOGQI hChLg GdQbGHI GdbVGFjI GdCNQi Ydi GdedGAeI (B: (3hbO NUU GdaUd GdChd dOQGSI bVGA GdZdh hYdGbJg HGdSdWI GdJbOjQjI ddEOGQI(B: (3ceG JfGhd GdaUd GdKGfj YdGbI bVGA GdZdh HChLg GdQbGHI GdbVGFjI GdCNQi Ydi GdedGAeI (B: (3cPdc JfGhd GdHGH GdKGfj hGdCNjQ (B: (3fTCI bVGA GdZdh aj abg hCMcGe cd ef GdbVGA GdEOGQj GdeUQj hGddjHj(B: (3hbO NUU GdaUd GdChd dOQGSI fTCI hJWhQ QbGHI GdZdh aj GdbVGA GdEOGQj GdeUQj (B: (3ceG JfGhd GdaUd GdKGfj fTCI hJWhQ bVGA GdZdh aj GdbVGA GdEOGQj GddjHj (B: (3hCNjQG CfgjfG OQGSJfG HNGJeI JVefJ Cge GdfJGFL hGdJhUjGJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe (B2013s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdEOGQjs; (3GdLRGA GdJCOjHj s; (3GdSdWI GdJbOjQjI s; (3GdeNGdaI GdJCOjHjIs; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3cdjI GdMbhbs